Influence of Solar Wind Parameters on Equatorial Magnetic Observatories during Intense Geomagnetic Storms of the Year 2015 (Journal of Scientific Research, 2020)
Coronal mass ejection (CME) and Corotating interaction region (CIR), a dynamic phenomenon associated with the sun, is widely acknowledged as the main causative factor for the occurrence of the geomagnetic storms. In the present investigation, we studied the influence of solar wind parameters and interplanetary magnetic field (IMFBz) on two severe geomagnetic storms (Dst=0.8) with the H-comp. Dynamic spectrum of H-component of magnetic field at low latitudes and solar wind parameters reveals a burst-like nature during the main phase of these storms. During Ionospheric Disturbance Dynamo (Ddyn) for March Storm, it is observed that American sector has downward movement in H-component of magnetic field and prominent attenuation of EEJ in African and Indian sectors. Similarly, for June storm, downward H-component movement is observed in both the American and African sectors and attenuation of EEJ at Indian sector.